Strategies for improving adipose-derived stem cells for tissue regeneration. Issue 1 (16th August 2022) - Yuan, Xin; Li, Li; Liu, Haofan; Luo, Jing; Zhao, Yongchao; Pan, Cheng; Zhang, Xue; Chen, Yuwen; Gou, Maling
Abstract: Adipose-derived stem cells (ADSCs) have promising applications in tissue regeneration. Currently, there are only a few ADSC products that have been approved for clinical use. The clinical application of ADSCs still faces many challenges. Here, we review emerging strategies to improve the therapeutic efficacy of ADSCs in tissue regeneration. First, a great quantity of cells is often needed for the stem cell therapies, which requires the advanced cell expansion technologies. In addition cell-derived products are also required for the development of 'cell-free' therapies to overcome the drawbacks of cell-based therapies. Second, it is necessary to strengthen the regenerative functions of ADSCs, including viability, differentiation and paracrine ability, for the tissue repair and regeneration required for different physiological and pathophysiological conditions. Third, poor delivery efficiency also restricts the therapeutic effect of ADSCs. Effective methods to improve cell delivery include alleviating harsh microenvironments, enhancing targeting ability and prolonging cell retention. Moreover, we also point out some critical issues about the sources, effectiveness and safety of ADSCs. With these advanced strategies to improve the therapeutic efficacy of ADSCs, ADSC-based treatment holds great promise for clinical applications in tissue regeneration.